Pengaruh Budaya Organisasi dan Stres Kerja Terhadap Produktivitas Kerja Pegawai pada Dinas Pekerjaan Umum dan Penataan Ruang Kota Bima - Ardiansyah; Mukhlis (LANCAH: Jurnal Inovasi dan Tren, 2023)
This study aims to determine and analyze the effect of organizational culture and work stress on employee work productivity at the Department of Public Works and Spatial Planning in the City of Bima. type of associative research with a Likert scale questionnaire as an instrument. The population in this study were all employees at the Public Works and Spatial Planning Office of the City of Bima, totaling 122 people. With details of 71 employees who are ASN and 51 honorary employees. The sample in this study were 71 employees (ASN) at the Public Works and Spatial Planning Office of the City of Bima. The sampling technique used was saturated sampling. Data collection techniques used were observation, questionnaires and literature study. Hypothesis testing using the t test and f test. The results of the study show that organizational culture and work stress have a significant effect on employee work productivity at the Public Works and Spatial Planning Office of the City of Bima